Hypoxia-tolerant polymeric photosensitizer prodrug for cancer photo-immunotherapy - Jie Yu; Jiayan Wu; Jingsheng Huang; Cheng Xu; Mengke Xu; Clarence Zhi Han Koh; Kanyi Pu; Yan Zhang (Nature Communications)
Abstract Although photodynamic immunotherapy represents a promising therapeutic approach against malignant tumors, its efficacy is often hampered by the hypoxia and immunosuppressive conditions within the tumor microenvironment (TME) following photodynamic therapy (PDT). In this study, we report the design guidelines towards efficient Type-I semiconducting polymer photosensitizer and modify the best-performing polymer into a hypoxia-tolerant polymeric photosensitizer prodrug (HTPSNiclo) for cancer photo-immunotherapy. HTPSNiclo not only performs Type-I PDT process to partially overcome the limitation of hypoxic tumors in PDT by recycling oxygen but also specifically releases a Signal Transducer and Activator of Transcription-3 (STAT3) inhibitor (Niclosamide) in response to a cancer biomarker in the TME. Consequently, HTPSNiclo inhibits the phosphorylation of STAT3, and suppresses the expression of hypoxia-inducible factor-1α. The synergistic effect results in the enhanced activation of immune cells (including mature dendritic cells, cytotoxic T cells) and production of immunostimulatory cytokines compared to Type-I PDT alone. Thus, HTPSNiclo-mediated photodynamic immunotherapy enhances tumor inhibition rate from 75.53% to 91.23%, prolongs the 100% survival from 39 days to 60 days as compared to Type-I PDT alone. This study not only provides the generic approach towards design of polymer-based Type-I photosensitizers but also uncovers effective strategies to counteract the immunosuppressive TME for enhanced photo-immunotherapy in 4T1 tumor bearing female BALB/c mice.